The nominalization of the “scientist” during the Scientific Revolution - Laris Pardo, Jorge Alejandro (2025)
In the current historiography of science, of heavy Anglo-Saxon influence, it has become mandatory to point out that William Whewell (1794-1866) coined the word “scientist” in English in 1834, due to the difficulty of finding a voice equivalent to the German “natur-forscher”. The purpose of this article is to question whether it is correct to apply this reflection to the evolution of our word “científico/ca”. The study of this process of nominalization in Spanish is based on historical sources and digital tools such as the Corpus of the Historical Dictionary of the Spanish Language (CDH), the Diachronic Corpus of Spanish (CORDE) and the New Lexicographic Treasure of the Spanish Language (NTLLE) of the Royal Academy of the Spanish Language; the Dictionary of Science and Technique of the Renaissance of the University of Salamanca; as well as the Google Ngram database. These searches have been complemented with testimonies that the author has collected throughout his research and a dialogue with the relevant historiography.. It is concluded that the evolution of our word “científico/ca” does not correspond to the Anglo-Saxon one. On the contrary, its origin is found in a long process of nominalization.